Good governance in India - Barthwal, C. P. (New Delhi : Deep & Deep, 2003)
'The present book is the result of the papers presented by the resources persons and participants at the 3-Weeks long Refresher Course in Public Administration / Political Science held in June 2002 under the aegis of the UGA-Academic Staff College, Lucknow University with the editor of the present book as its coordinator. Some papers were later added to fill in the areas not covered in the Refresher Course'
Includes bibliographical references and index
Keywords: Public administration -- India; India -- Politics and government -- 20th century